HUKUM DAN PERUBAHAN SOSIAL: STUDI SOSIOLOGI HUKUM TENTANG PERAN GENERASI Z DALAM REFORMASI KEBIJAKAN PUBLIK - Habibullah, Fayyad (LPPM Universitas Bina Bangsa, 2025)
The formulation of the Successor heirs is regulated in article 185 of the Compilation of Islamic Law, This research examines the role of Generation Z in public policy reform through digital technology, focusing on the sociology of law. Generation Z utilizes social media and digital platforms to advocate for legal changes, creating a new space for more inclusive and direct social participation. The impact of digital technology in social movements has transformed the relationship between law, technology, and society, making law more responsive to social dynamics. This study contributes to the theory of sociology of law, offering a more dynamic perspective based on the digital behavior of the younger generation. The findings are expected to enrich the sociology of law and provide recommendations for policymakers to accommodate Generation Z's active role in the policy reform process.